The severity of valvular heart disease in euthyroid individuals is associated with thyroid hormone levels but not with TSH levels - Wang, Pin; Lu, Sen; Yang, Yan; Liu, Limei; Zhou, Guangpeng; Zhu, Jieling; Niu, Diejing; Wang, Yi; Wang, Shaohua (Frontiers in Endocrinology, 2023)
Background: Abnormal thyroid function is a metabolic disorder and can lead to several complications, including cardiovascular diseases. In this study, we aimed to examine the relationship between clinical traits and outcomes and the thyroid hormone level of euthyroid individuals with valvular heart disease (VHD). Method: The thyroid function was evaluated in 526 euthyroid VHD patients and 155 healthy control people. As well as clinical indicators were collected and analyzed. Results: No difference in TSH levels (p>0.05) was recorded; however, fT3, TT3, and TT4 levels were lower in the euthyroid VHD patients than in healthy control(4.3 vs 4.63; 1.37 vs 1.48; 97.7 vs 102.09, respectively, all p＜0.05), while the fT4 level was higher (12.91 vs 12.35, p＜0.05). Moreover, all showed a continuous trend with the change of NYHA grade which does not consist of the incidence of euthyroid sick syndrome(ESS). Further analysis showed that for every 10-fold increase in BNP, fT4 increases by 83%, fT3 decreases by 30%, and TT3 decreases by 12% after being adjusted for other influencing factors. Meanwhile, adjusted fT4 was correlated with multiple worse clinical indicators, which were influenced by age. Conclusion: Thyroid hormones are widely regulated in VHD patients even with acceptable cardiac function, except for TSH level. And the adjusted fT4 is related to worse clinical indicators and outcomes which are only recorded in patients under 53 years old.